PENGARUH KEPEMIMPINAN VISIONER KEPALA SEKOLAH TERHADAP KINERJA GURU SMP NEGERI 12 SIGI - Beddu, Abidin (Katalogis, 2016)
The purpose of this research is to know and analyze the effect of the visionary leadership of headmaster on teacher performance. The populations of this research are headmaster and all teachers with a total population of 39 people. Due to population was relatively limited, then to ensure the accuracy of the data, the author determined the entire member population is as the sample, using census method. The type of data in this study consisted of qualitative and quantitative data with the source used consisting of primary and secondary data. The data collection techniques used were observation, questionnaires, and documentation. To answer the research hypothesis, the data analysis technique used is multiple linear regression analysis; the results showed that visionary leadership headmaster significantly affect on teacher’s performance, with the value of the F-count amount 56.115 with a significance level of 0.000. When compared to the value of the F-count (56.115) with the F-table (1.84) at a significance level of α 0.05, it means that variable visionary leadership of headmaster which consists of the ability to determine the direction the organization (X1), understand the wishes of the people or consumers (X2), effected in activity and become a guide (X3) and be able to anticipate the future become an agent of change (X4) simultaneously significantly affect on teacher’s performance at SMPN 12 Sigi.